O multiletramento como estratégia de ensino na inclusão dos estudantes com deficiência intelectual e autismo das Escolas do Campo - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2024)
This research presents the main question: How can pedagogical practices involving multiliteracy contribute to the educational formation of students with intellectual disabilities and autism in rural schools, specifically at Nicolau Morais de Castro Municipal School in Campo Largo, PR? The general objective is to understand how pedagogical practices involving multiliteracy can contribute to the education of students with intellectual disabilities and autism at Nicolau Morais de Castro Municipal School in Campo Largo, PR. The specific objectives are: To understand the educational reality and pedagogical practices developed by teachers at Nicolau Morais de Castro Municipal School for students with intellectual disabilities and autism. To comprehend the possibilities and challenges of pedagogical practices for students with intellectual disabilities and autism in rural schools through the pedagogy of multiliteracy. To propose that teachers incorporate multiliteracy-based pedagogical practices for students with intellectual disabilities and autism in rural schools. As an educational resource, the research aims to develop a guiding document with teaching strategies that include multiliteracy to support the learning of students with intellectual disabilities and autism. The methodology involves a qualitative and quantitative approach, descriptive and exploratory in nature, and includes bibliographic surveys and fieldwork through a focus group study with teachers of autistic students and those with intellectual disabilities. This is based on a critical-reflective construction informed by theories from multiliteracy researchers (Roxane Rojo), rural education (Miguel Arroyo; Roseli Caldart; Mônica Molina), and pedagogical practice (Maria Antônia de Souza). The discussions within the group addressed the following themes: rural schools, public policies, pedagogical practice, and special education in rural areas. From this analysis, data was collected to develop the educational resource "Guiding Document: Teaching Strategies for Including Students with Intellectual Disabilities and Autism in Rural Schools." The document provides strategies for working with students with intellectual disabilities as well as for those with autism, based on the discussions raised by the focus group. We understand that it is possible to conduct work where both groups of students benefit, with teaching strategies that can be adapted for the entire class, involving basic concepts for human development, thereby ensuring the inclusion of students with intellectual disabilities and autism.
Keywords: Escolas do Campo; Educação Especial; Multiletramento; Prática Pedagógica; Deficiência Intelectual e autismo; Rural Schools; Special Education; Multiliteracy; Pedagogical Practice; Intellectual disability; CNPQ::CIENCIAS HUMANAS::EDUCAÇÃO